2017
DOI: 10.1016/j.repbio.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Non-esterified fatty acids in early luteal bovine oviduct fluid mirror plasma concentrations: An ex vivo approach

Abstract: We investigated whether and to which extent plasma non-esterified fatty acids (NEFAs) are reflected in oviduct fluid (OF) using an improved ex vivo flushing method. OF and plasma NEFA concentrations were respectively 0.29±0.19 and 0.31±0.14mmol/L, they didn't differ significantly (P=0.13) and tended to be positively correlated (Pearson correlation coefficient=0.56; P=0.07). Results suggest that OF NEFAs mirror the concentrations seen in plasma of healthy cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Intensive energy demand is often manifested through elevated non-esterified fatty acids (NEFAs) in the circulating blood. In healthy cattle, levels of NEFAs in the tubal fluid mirror the concentrations measured in plasma [30], meaning that, in the case of lipolytic metabolism during the periconceptional period, the early embryo is likely exposed to elevated NEFAs. Elevated levels of NEFAs were shown to affect embryo DNA methylation and gene expression [103].…”
Section: Metabolism and Energy Balancementioning
confidence: 85%
See 1 more Smart Citation
“…Intensive energy demand is often manifested through elevated non-esterified fatty acids (NEFAs) in the circulating blood. In healthy cattle, levels of NEFAs in the tubal fluid mirror the concentrations measured in plasma [30], meaning that, in the case of lipolytic metabolism during the periconceptional period, the early embryo is likely exposed to elevated NEFAs. Elevated levels of NEFAs were shown to affect embryo DNA methylation and gene expression [103].…”
Section: Metabolism and Energy Balancementioning
confidence: 85%
“…The embryo lipid reserve may be of particular importance in species with long preimplantation period such as pigs, cattle, dogs, and horses. Oviductal secretions contain a variety of lipids, including cholesterol, triglycerids, and fatty acids [30]. The OF contains also L-carnitine, which is required for the beta-oxydation of these lipids, while albumin as well as high-(HDLs) and low-density lipoproteins (LDLs) play the role of lipid carriers in OF [25,31].…”
Section: Lipidsmentioning
confidence: 99%
“…During the early luteal phase, OF is composed of cholesterol, triglycerides, non-esterified fatty acids (NEFA), proteins, glucose, and lactate. OF and plasma have similar concentrations of NEFA in healthy cows that probably alter the lipid composition of oviduct cells [88]. Alterations in the oviduct microenvironment can affect embryo development; thus, it is comprehensible that alterations in feed composition also affect pregnancy establishment.…”
Section: Tubal Fluidsmentioning
confidence: 99%
“…In order to evaluate the effect of elevated NEFA exposure during sperm capacitation (4 h) and fertilization (22 h), fertilization medium was supplemented with the following NEFA treatments: i) STANDARD: FA-free and solvent-free medium, ii) SOLVENT: FA-free medium with 0.45 % absolute ethanol, Since no data are available regarding the concentrations of FFAs in oviductal fluid in cows under metabolic stress conditions, the concentrations of FFAs used here are based on serum concentrations in cows during NEB (Leroy et al 2005) which may correlate with the oviductal fluid concentrations (Jordaens et al 2017a). A basal NEFA treatment group was implemented as a control in this study in order to improve the physiological relevance of our in vitro model as these NEFAs are present at basal concentrations in the environment in which oocytes mature and embryos develop in vivo (Leroy et al 2005).…”
Section: Experimental Designmentioning
confidence: 99%
“…Likewise, early bovine embryos are highly sensitive to changes in their micro-environment, the oviduct (Rizos et al 2003;Leese et al 2008). As the maternal metabolic state is reflected in blood and follicular fluid, it may furthermore influence oviductal fluid composition; a recent study showed that NEFAs are present in the oviductal fluid and mirror the concentrations seen in plasma of healthy cows (Jordaens et al 2017a). Although the oviduct has been suggested to modulate its micro-environment by alleviating potential lipotoxic effects (Jordaens et al 2017b), it remains debatable whether this gatekeeper function is sufficient to actually protect the embryo from an adverse climate.…”
Section: Introductionmentioning
confidence: 99%